NiO hollow microspheres interconnected by carbon nanotubes as an anode for lithium ion batteries. (20th September 2016) - Cao, Wen; Hu, Aiping; Chen, Xiaohua; Liu, Xiaohong; Liu, Peng; Tang, Qunli; Zhao, X.S.
Abstract: In this work, NiO hollow microspheres interconnected by multi-walled carbon nanotubes (MWCNTs) were prepared, characterized, and evaluated in terms of lithium ion storage properties. Characterization results showed that the NiO hollow microspheres were formed by self assembly of NiO nanoparticles promoted by MWCNTs, which connected the NiO microspheres to form a long-range network. Electrochemical measurement results showed a charge capacity as high as 597.2 mAh g −1 when cycling at the rate 2 C and maintained 85.3% capacity of 0.1 C. After cycling for 100 times at 1 C, it maintained a capacity of 692.3 mAh g −1 with retention 89.3% of the initial capacity. The observed excellent electrochemical performance is attributed to the presence of MWCNTs interconnecting the NiO microspheres of the composite material, of which electronic conductivity was improved, and the mesoporous hollow structure effectively alleviated the volume changes to maintain the structural stability during cycling.